PENGARUH LATIHAN BERLARI ZIG ZAG MELEWATI CONE TERHADAP KETERAMPILAN DRIBBLE PADA SSB PUMA FC U-12 - Aldirus Difedema Fidel; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the problems stated above, the problem can be formulated as follows: Does the ZIG ZAG Running Cone Pass practice affect the SSB Puma Fc U-12 dribble skills. The sample is simply interpreted as part of the population that is the actual data source in a study. According to Hadi (1993: 321) "if the population is less than 100 it is better for all sample populations, then if the population is more than 100 then the sample is at least 10-25%. Based on the analysis carried out, the value between the initial test and the final test of the zigzag running exercise passes the cone to the speed with a significant level of 0.05 with degrees of freedom N - 1 (16) indicating that the value (32.00) It can be concluded that the hypothesis states that there is an effect of exercise running zigzag past the cone on the speed of the U-12 FCB Duma Dribble Skill. To get a good speed result, one of the exercises that can increase speed is by practicing running zigzag past the cone. The method of practicing running zigzags through cones is one of the speed exercises that is useful for increasing running speed, because the mechanism of the training moves mostly involves muscle muscle. Based on the results of the study it can be concluded that there is an effect of the exercise running zigzag past the cone which is significant to the increase in speed. Training is programmed and continues, the more routine we do the Zig Zag Running Exercise Through Cone, the better our speed, especially in football that really needs speed in the game.Keywords: Running Zig Zag, Dribble Skills